Curcumin Modifies Epithelial–Mesenchymal Transition in Colorectal Cancer Through Regulation of miR-200c/EPM5 - Wang H (Cancer Management and Research, 2020)
Hui Wang, Xiaolong Cai, Longyang Ma Department of Emergency Surgery, Shaanxi Provincial People’s Hospital, Xi’an, Shaanxi Province, People’s Republic of ChinaCorrespondence: Longyang Ma Email longyangma@hotmail.comBackground: The serious side effect of current conventional treatments for patients with metastatic colorectal cancer (CRC) highlights the requirement of an alternative treatment strategy. Natural compounds, such as curcumin, have been gained much attention due to its low toxicity and anti-tumor effect.Methods: qPCR and Western blot were used to measure the molecular changes induced by curcumin. Wound-healing assay and transwell assay were conducted to study the effect on cell migration and invasion. RT1 PCR array was performed to identify the miRNAs involved in curcumin-repressed EMT. Three algorithms and luciferase reporter assay were used to identify EPM5 as a target of miR-200c. The bioinformatical analysis of TCGA-COAD and other CRC cohorts were used to examine the association of EPM5 with EMT signatures and clinical relevance. The ectopic expression or siRNA-mediated knockdown of EPM5 was applied to study the role of EPM5 in CRC.Results: Treatment with curcumin changed the epithelial–mesenchymal transition (EMT)-related gene expression, repressed cell migration and invasion in CRC cells. Its anti-tumor capability required the upregulation of miR-200c. EPM5 was a direct target of miR-200c and enriched in the consensus molecular subtype (CMS) 4 of CRC. Ectopic expression of EPM5 alone was sufficient to induce EMT in CRC. Downregulation of EPM5 was necessary for curcumin-repressed EMT, migration, and invasion. Higher expression of EPM5 was associated with the advanced TNM stages and poor survival in CRC.Conclusion: Our data provide the first evidence that the curcumin inhibits EMT in CRC by upregulation of miR-200c and downregulation of EPM5, and the use of curcumin might be able to prevent or delay CRC progression.Keywords: curcumin, EMT, miR-200c, EPM5, CRC